(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This publication is the result of a two-and-a-half-year process that has drawn together critical thinking and practical experience concerning agriculture and wetland interactions. The process began at the Ramsar Conference of Parties (COP) 9 in Uganda, involve a workshop in Wageningen in early 2006, saw the development of a team of Wetland Action and Wageningen University researchers.
Keywords: Wetland agriculture,Sustainable agriculture,Đất ngập nước nông nghiệp,Nông nghiệp bền vững